The Effect of Current Ratio, Net Profit Margin and Debt to Equity Ratio to Prfit Growth In Subsector Food and Beverages Companies Registered at the Indonesia Stock Exchange Period 2017-2021 - Febiyola Wijaya; Pujiarti Pujiarti (Komunitas Dosen Indonesia, 2023)
In writing this research intends to determine the effect caused by the CR, NPM, and DER on Profit Growth in companies in the food and beverage subsector. In this thesis research, the writer uses purposive sampling method and software statistic SPSS 25 to process the data. This study uses a population, namely food and beverage sub-sector companies listed on the IDX for the 2017-2021 period. The number of samples in this research were 6 companies over a 5 year so that a total of 30 samples were collected. In the research the results shown are that the variable CR (X1) obtains 0.515 which means it does not significantly affect profit growth, 0.045 for NPM (X2) which means it has a significant effect on profit growth, 0.640 for DER (X3) which means no significant effect on profit growth